MINYAK GOSOK DAPAT MENGOBATI STOMATITIS APTOSA REKUREN SECARA TOPIKAL - Ali Yusran; Donald RN (Journal of Dentomaxillofacial Science, 2002)
Many studies have been done to get the right material in the treatment of recurrent minor aphthous stomatitis, butthe result still unsatisfied.The aim ofthistudy was to know the influence applicationof rubbing oil against the healing and comportable atrecurrent minor aphthous stomatitis. This study was aclinical observasionally and healing was resulted in aboutfour days. The use of topical rubbing oil in the treatment ofrecurrent minor aphthous stomatitis could avoid infection.